Forming of Personality’s Moral Culture in Professional Training Process - Halyna Boryn (Pedagogical Discourse, 2012)
The scientists’ opinions to the problem of the student’s moral culture forming under the conditions of professional training to future professional activity are analyzed in the article, and the main ways for cultural development of future specialist personality in educational process of higher educational institution are determined.